Rancang Bangun Aplikasi Akuntansi Pinjaman Anggota Koperasi Kencana Cirebon - Akbari, Safitri; Suwandi, Suwandi; Turini, Turini; Septian, Willy Eka (JDMIS: Journal of Data Mining and Information Systems, 2023)
One of the activities in the Employee Cooperative is to provide credit loans to its members, in accordance with one of the goals of the Cooperative establishment, namely to provide welfare for members. The purpose of this research is to make a loan accounting application for members of the Kencana Cooperative, Cirebon City. The object of this research is the Kencana Cooperative, which is a cooperative owned by the National Population and Family Planning Agency (BKKBN) of Cirebon City. Data collection techniques that the author uses in this study are interviews, observation and literature study. Applications made using PHP programming (Hypertext Preprocessor) while for data storage using MySQL database. This research is very useful for the Kencana Cooperative of Cirebon City, because it can produce an accounting application that can be used as an internal control tool in terms of recording loans for cooperative members. This application can record all cooperative employee loan activities. The limitation of this research is that this application has not been able to make financial reports of the Kencana Cooperative, such as the Balance Sheet and Profit and Loss Statements. This research can contribute to the author, the Kencana Cooperative and the readers. This research focuses on the field of computerized accounting, so that writers and readers can add insight in the field of computerized accounting